Journey of Signs and Shop Signs From Prehistory to Digital Age - Nanki Nath (Cultural Syndrome, 2020)
The published research related to history of signs presents a generic commentary. Therefore, this paper presents a detailed scrutiny of the essence and the narrative behind the evolution of signs [focus: shop signs]. According to The Complete Encyclopedia of Signs and Symbols, ‘Signs are vehicles for information and meaning, operating on many different levels – the universal and particular, intellectual and emotional, spatial and temporal, spiritual and material.’ Later periods of human civilization witnessed a conscious shift from the traditional industry to a knowledge-based economy that inculcates information-digitization. These signs were not only reflections of owners’ tastes and personality, but also formed the ethnic makeup of a street market. Gradually in the digital age, commercially oriented signs started giving continuity to public spaces and built streetscapes. This paper brings forth an emergence of signs and shop signs in India, rest of the Asian Pacific Rim countries followed by European countries and finally the Western Pacific Rim countries in North and South America